Tax Evasion Between Tax Optimization at the Border of Legality, Tax Burden and Voluntary Compliance - Petrașcu, Daniela; Păcurariu, Ioana; Ciocanea , Bianca Cristina; Pițu, Cosmin Ioan (Journal of Legal Studies, 2023)
Tax evasion operates beyond the boundaries of the jurisdictions, it develops across borders, and the extent of tax fraud as a phenomenon is differentiated according to the aspects and the rigours of legislation, as well as according to the economic environment of each country in part. Regardless of the level of development of the country in which it manifests, the effects of the fiscal fraud are destructive, affecting both the state budget, as well as the financial resources of the offenders’ commercial partners. The fiscal fraud has negative effects over the economic market, and one of the consequences is the social inequality from the perspective of the abuse and the predisposition of certain taxable subjects to fraud. Certainly, the phenomenon remains unraveled, the financial schemes being extremely complex, and the fraud mechanisms are some of the most laborious ones and in a permanent improvement, while the evaders keep finding new means by way of which they illegally attract financial resources. The fight against tax evaders is a difficult one, mainly because of the sometimes “deliberate” legislative “loopholes”, but also because of their ingenuity, which is often “one step” ahead of those who fight against tax evasion.